Estudio comparado del desarrollo histórico de la Psicopedagogía en Cuba y Chile - Espinoza Vásquez, Rodrigo Alberto (2018)
Psychopedagogy is an interdisciplinary science with great growth in Latin American countries, but there are few studies that address its historical evolution, according to its peculiarities. The objective of this article was to carry out a comparative study of the historical development of the Psychopedagogy between Chile and Cuba, two Latin American nations that share a peculiar past and presentto determinate coincidences and differences. The historical background, institutionalization and national contributions wereselected as indicators, which allowed showing the similarities and differences according to the historical, economic, cultural and political development peculiar to each country, with a previous evolution of Psychology and Pedagogy. , as basal sciences, from the influences of foreign conceptions deeply rooted in the educational field, but with a creative, contextualized and successful work of professionals in Psychopedagogy, adapting them to the historical needs of each country and achieving the solution of educational problems and at the same time enrich this science. Psychopedagogy has a certain maturity as an interdisciplinary science in full development in the current conditions of Cuba and Chile.La Psicopedagogía constituye una ciencia interdisciplinar con gran auge en los países latinoamericanos, pero son escasos los estudios que abordan su evolución histórica, de acuerdo con sus peculiaridades. El objetivo de este artículo fue realizar un estudio comparado del desarrollo histórico de la Psicopedagogía entre Chile y Cuba, dos naciones latinoamericanas que comparten un pasado y un presente peculiares, para determinar coincidencias y diferencias. Se seleccionaron como indicadores los antecedentes históricos, la institucionalización y los aportes nacionales, los cuales permitieron evidenciardichas similitudes y diferencias, de acuerdo con el desarrollo histórico, económico, cultural y político peculiar en cada país, con una evolución previa de la Psicología y la Pedagogía, como ciencias basales, a partir de las influencias de concepciones foráneas de gran arraigo en el campo educativo, pero con una labor creativa, contextualizada y exitosa de los profesionales de la Psicopedagogía, al adecuarlas a las necesidades históricas de cada país y lograr la solución científica de los problemas educativos y a la vez enriquecer dicha ciencia. La Psicopedagogía posee cierta madurez como ciencia interdisciplinar en pleno desarrollo en las condiciones actuales de Cuba y de Chile